Efecto del tratamiento con acetonida de triamcinolona sobre la glucemia en gatos - Colla, C. (2011)
Cats have shown to be more resistant to the presentation of adverse reactions to glucocorticoids, although their particular sensibility to develop hyperglycemia could mean a greater diabetogenic effect on this species mainly during prolonged treatments. As bibliography on this area is scarce it was proposed to study the modifi cations on glycemia in cats (n=8) treated with a SC dose of triamcinolone acetonide (0.22 mg/kg). Glycemia levels were indirectly measured by plasma fructosamine immediately before the administration of the drug and on the 15th day. No signifi cant differences were detected between pre and post administration values; this fi nding suggests a normal control of glycemia after a parenteral single dose of the depot glucocorticoid.